Evaluation and Improvement of Metalurgy Key Performance Indicator at Concentrating Division PT. Freeport Indonesia - Arief, Orvelly Prima; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2015)
Abstract.With the current condition of mining business that highly influenced by the volatility of metal commodity prices including copper and gold, the competition between other companies in the same industry demanded that the production process to be effective in order to achieve higher profit. Maintaining the production process and has a correct performance measurement system is critical. Therefore a key performance indicator need to be evaluated and developed to help monitor the performance of metallurgy department, that will help to achieve the production target. The current key performance indicator system has provided the technical team or metallurgist at the Concentrating division with a tool to track various process parameters on a daily basis. However, there is an opportunity to create a better tool of performance tracking for improved productivity, has a simplicity in its display but containing enough detail for quick troubleshooting of the problems, has a specific performance indicators required for different level of responsibility, and easy to use to monitor the process and help to achieve production target. In order to find the right key performance indicator as required by the metallurgy department, a framework developed from performance measurement concept of total quality management is selected. Because of its ability to be more focused on the improvement of internal business process. The critical success factor are used for the basis of selecting all parameters for the key performance indicator. The critical success factor can be identify and defined based on the mission of the metallurgy department and its business strategies. Combined with mineral processing theory to confirm and select the parameters used for metallurgy key performance indicators.Â Keywords: Metallurgy, Key Performance Indicators (KPI), Performance Measurement Framework, Critical Success Factor.Â